Gastrointestinal helminths in slaughtered cattle in Ibadan, South-Western Nigeria (2014)
As part of an ongoing project to investigate the epidemiology of gastrointestinal helminths of cattle in Nigeria, we carried out a systematic random sampling of cattle slaughtered in a major abattoir in Ibadan, south-western Nigeria. Using sedimentation and floatation methods, we analyzed fecal samples from 397 animals between March and May 2013. Overall, 163 (41.6%) of the animals had at least one astrointestinal helminth egg, comprising a total of eight helminths from different genera (i.e., four nematodes, three trematodes, and one cestode), with nematode infection being the highest (71.54%). In addition, eggs of four helminths of zoonotic importance were also obtained. Among the cattle examined, the Bunaji breed was the most infected (46%; 69/150). Furthermore, female animals (OR = 1.1; 95% CI: 0.60–1.84) and animals with moderate body condition (OR = 1.2; 95% CI: 0.80–1.79) are more likely to be positive to helminth infection. Our findings reveal that there were helminth infections of both zoonotic and socioeconomic importance among the cattle screened. Considering the impact of the infections on animal production and public health, we advocate that effective prophylactic measures be adopted as a first step to curtail helminth infections of cattle in Nigeria.